The effects of trade liberalisation policy on the transport sector o f Uganda : case study: Road Transport Mode, 1994-1999 - Mpungu, Abed Kateete (Kampala : Makerere University, 2000)
Dissertation (B.Sc., Quant.Econ.) - Makerere University, 2000
Includes bibliographical references (p.39)
Keywords: Transportation and state -- Uganda